Comparative morphological trade-offs between pre- and post-copulatory sexual selection in Giant hissing cockroaches (Tribe: Gromphadorhini) - Durrant, Kate L.; Skicko, Ian M.; Sturrock, Craig; Mowles, Sophie L. (Nature Publishing Group, 2016)
Sperm competition theory predicts that animals face a trade-off between investment in weaponry and investment in ejaculate composition. Within the Madagascan giant hissing cockroaches (Tribe Gromphadorhini) differences in morphology exist that may indicate differing strategies of male-male competition. We compared relative pronotal horn length using high-resolution X-ray CT scanning data, relative testes mass, and male-male agonistic behaviour between two species of hissing cockroaches, Gromphadorhina oblongonota and Aeluropoda insignis. The gross morphology and behaviour of these two species indicated that G. oblongonota is selected for pre-copulatory mate acquisition and that A. insignis is selected for post-copulatory sperm competition. We found evidence for a trade-off when investing in testes mass vs. horn length between the species. The large, aggressive G. oblongonota follows a strategy of greater investment in weapons at the expense of testes mass while the smaller, less-aggressive A. insignis invests in relatively greater testes mass and less in pronotal weapon length. We also found evidence of a trade-off within each species, where individuals invest more heavily in weapon length at the expense of testes mass. These findings support the predictions of pre- and post-copulatory competitive investment trade-offs for a relatively understudied Tribe of cockroaches.